Imaging Genetic Based Mediation Analysis for Human Cognition - Chen, Tingan; Mandal, Abhishek; Zhu, Hongtu; Liu, Rongjie (Frontiers in Neuroscience, 2022)
The brain connectome maps the structural and functional connectivity that forms an important neurobiological basis for the analysis of human cognitive traits while the genetic predisposition and our cognition ability are frequently found in close association. The issue of how genetic architecture and brain connectome causally affect the human behaviors remains unknown. To seek for the potential causal relationship, in this paper we carried out the causal pathway analysis from single nucleotide polymorphism (SNP) data to four common human cognitive traits, mediated by the brain connectome. Specifically, we selected 942 SNPs which are significantly associated with the brain connectome, and then estimated the direct and indirect effect on the human traits for each SNP. We found out that a majority of the selected SNPs have significant direct effects on human traits and discussed the trait-related brain regions and their implications.